Adoption of financial technology in Islamic crowd-funding: predicting small and medium-sized enterprises’ intention to use the investment account platform - Md Husin, Maizaitulaidawati; Haron, Razali; Aziz, Shahab (IGI Global, 2021)
The purpose of this chapter is to examine the factors that influence small and medium-sized enterprises’ (SMEs) intentions to use the investment account platform (IAP) based on technology acceptance model (TAM). The central hypothesis for this chapter was that SMEs’ intentions to use IAP were a result of perceived usefulness and perceived ease of use. This chapter also suggested that perceived ease of use and intention was mediated by perceived usefulness of the IAP. Using primary data collection method, 163 questionnaires were collected from SMEs in Kuala Lumpur, Malaysia using the purposive sampling technique. The data were analysed using SPSS and SmartPLS. The chapter found that perceived ease of use had significant influences on SMEs intention to use the IAP while perceived ease of use significantly affected perceived usefulness and the relationship between perceived ease of use and intention was mediated by perceived usefulness of the IAP. The results of this chapter suggested strategies to promote the platform as a fund seeking platform for SMEs.